Prothrombotic states in women with infertility and psychosomatic disorders - Kaminskyi, A. V.; Boychuk, O. G.; Kolomiichchenko, T. V. (Regulatory Mechanisms in Biosystems, 2018)
Failures of in vitro fertilization (IVF) may be associated with prothrombotic states, the circulation of antiphospholipid antibodies (APA). 93 women with infertility were screened: the first group 32 women without severe psychosomatic disorders; the second group 61 women with psychosomatic disorders. The control group consisted of 30 fertile women. We carried out measurements in the blood serum of the level of AFA to membrane phospholipids (phosphatidylethanolamine, phosphatidylserine, cardiolipinum), antibodies to β2-glycoprotein (Iβ2-GPI), hemostasis (platelet count, ADP-induced platelet aggregation index, fibrinogen concentration, prothrombin index, activated partial thromboplastin time APTT, test for soluble fibrin-monomeric complexes, D-dimer), homocysteine, molecular genetic study of polymorphous variants for β-fibrinogen (C148T, 455GA) genes. The frequency of significant AFA titres in the group of women without psychosomatic disorders was 18.9%, and in women with psychosomatic disorders 44.3%, the rate of β2-GPI 9.6% in the first group versus 24.5% in the second group. Only in 11.5% of women in the second group elevated levels of APA were associated with β2-GPI and/or one or more clinical criteria for antiphospholipid syndrome (APS). In patients with infertility and psychosomatic disorders, we found increased platelet aggregation in the context of relative thrombocytopenia, higher fibrinogen levels, soluble fibrin-monomeric complexes, and prolonged APTT with elevated D-dimer levels. Some patients had hyperhomocysteinemia. In patients with psychosomatic disorders, the frequency of the minor alleles of the locus C148T and 455GA of the β-fibrinogen gene was greater than 40% (25–30% in first group). We distinguished factors that adversely affect the efficiency of IVF in the patients with psychosomatic disorders: elevation of APA; reduction in the number of thrombocites; growth of the ADP-induced aggregation index; extension of APTT; increase of fibrinogen, D-dimer; homocysteine; the presence of the minor allele of the T polymorphic locus C148T of the β-fibrinogen gene. The presence of prothrombotic states associated with APS should be taken into account when preparing for IVF and the appropriate correction should be made for them.